Membrane Processing and Steady-State Regulation of the Alternative Peroxisomal Import Receptor Pex9p - Rudowitz, Markus; Erdmann, Ralf; Schliebs, Wolfgang (Frontiers in Cell and Developmental Biology, 2020)
Import of peroxisomal matrix proteins with a type 1 peroxisomal targeting signal (PTS1) in Saccharomyces cerevisiae is facilitated by cytosolic import receptors Pex5p and Pex9p. While Pex5p has a broad specificity for all PTS1 proteins independent of the growth conditions, Pex9p is only expressed in fatty-acid containing media to mediate peroxisomal import of the two malate synthases, Mls1p and Mls2p, as well as the glutathione transferase Gto1p. Pex5p-cargo complexes dock at the peroxisomal membrane, translocate their cargo-protein via a transient pore and are recycled into the cytosol for a further round of import. The processing of Pex5p has been shown to require a complex network of interactions with other membrane-bound peroxins, as well as decoration with ubiquitin as signal for its ATP-dependent release and recycling. Here, we show that the alternative receptor Pex9p requires the same set of interacting peroxins to mediate peroxisomal import of Mls1p. However, while Pex5p is rather stable, Pex9p is rapidly degraded during its normal life cycle. The steady-state regulation of Pex9p, combining oleate-induced expression with high turnover rates resembles that of Pex18p, one of the two co-receptors of the PTS2-dependent targeting pathway into peroxisomes. Both Pex9p- and Pex18p-dependent import routes serve the fast metabolic adaptation to changes of carbon sources in baker´s yeast. By sequence similarities, we identified another Pex9p homolog in the human pathogenic fungus Candida glabrata, in which similar metabolic reprogramming strategies are crucial for survival of the pathogen.